Phytochemistry and Biological Activities of Poria - Jie Lu; Jing Tian; Li Zhou; Lijun Meng; Sitan Chen; Changyang Ma; Jinmei Wang; Zhenhua Liu; Changqin Li; Wenyi Kang (Journal of Chemistry)
Poria is a common Traditional Chinese Medicine in clinic. In recent years, the chemical and pharmacological studies of Poria have made great progress, triterpenes and polysaccharides have been isolated, and various types of compounds containing lipids, octanoic acids, fatty acids, and trace elements have been found. In this paper, we reviewed the literature, summarized the main compound types, and reviewed in detail their pharmacological effects in antitumor, immunomodulatory, effects on kidney, hepatoprotective activity, effects on blood sugar, antioxidant effects, anti-inflammatory effects, effects on the gut, antidepressant, and so on, and also categorized the compounds with the same or similar pharmacological effects to provide a reference for the in-depth study of the material basis of the pharmacological effect, quality standards, and pharmacological activity of Poria.